The Multiple Relationships Between Anxiety Sensitivity, Social Support, Perception of Pain and Life Expectancy Variables - Zohreh Latifi; Mahnoosh Kiani (Gonabad University of Medical Sciences, 2021)
Background: The aim of this correlational study was to investigate the multiple relationships between anxiety sensitivity, social support, and perception of pain with life expectancy.  Methods: The statistical population consisted of all older adults in Isfahan (males and females) in spring 2016, of whom 250 individuals were selected by convenience sampling method from different places. In order to measure the variables, Hope Based on Islamic Sources, Perceived Social Support, Anxiety Sensitivity, and the Perception of Pain questionnaires were used. Data analysis was conducted by Pearson correlation and simultaneous multiple regression analysis.  Results: The results indicated that there was a significant positive relationship between anxiety sensitivity, social support, and the perception of pain with life expectancy (P<0.01).  Conclusion: This result implies that social protection enhancement, not only increases hope but also affects the fear of one's anxiety observed by others, the perception of pain, and the fear of lack of cognitive control.